Signaling mechanism underlying the histamine‐modulated action of hypoglossal motoneurons. Issue 2 (1st March 2016) - Liu, Zi‐Long; Wu, Xu; Luo, Yan‐Jia; Wang, Lu; Qu, Wei‐Min; Li, Shan‐Qun; Huang, Zhi‐Li
Abstract: Histamine, an important modulator of the arousal states of the central nervous system, has been reported to contribute an excitatory drive at the hypoglossal motor nucleus to the genioglossus (GG) muscle, which is involved in the pathogenesis of obstructive sleep apnea. However, the effect of histamine on hypoglossal motoneurons (HMNs) and the underlying signaling mechanisms have remained elusive. Here, whole‐cell patch‐clamp recordings were conducted using neonatal rat brain sections, which showed that histamine excited HMNs with an inward current under voltage‐clamp and a depolarization membrane potential under current‐clamp via histamine H1 receptors (H1 Rs). The phospholipase C inhibitor U‐73122 blocked H1 Rs‐mediated excitatory effects, but protein kinase A inhibitor and protein kinase C inhibitor did not, indicating that the signal transduction cascades underlying the excitatory action of histamine on HMNs were H1 R/Gq/11 /phospholipase C/inositol‐1, 4, 5‐trisphosphate (IP3 ). The effects of histamine were also dependent on extracellular Na + and intracellular Ca 2+, which took place via activation of Na + ‐Ca 2+ exchangers. These results identify the signaling molecules associated with the regulatory effect of histamine on HMNs. The findings of this study may provide new insights into therapeutic approaches in obstructive sleep apnea. We proposed the post‐synaptic mechanisms underlying the modulation effect of histamine on hypoglossal motoneuron. Histamine activates the H1 Rs via PLC and IP3, increases Ca 2+ releases from intracellular stores, promotes Na + influx and Ca 2+ efflux via the NCXs, and then produces an inward current and depolarizes the neurons. Histamine modulates the excitability of HMNs with other neuromodulators, such as noradrenaline, serotonin and orexin. We think that these findings should provide an important new direction for drug development for the treatment of obstructive sleep apnea. Abstract : We proposed the post‐synaptic mechanisms underlying the modulation effect of histamine on hypoglossal motoneuron. Histamine activates the H1 Rs via PLC and IP3, increases Ca 2+ releases from intracellular stores, promotes Na + influx and Ca 2+ efflux via the NCXs, and then produces an inward current and depolarizes the neurons. Histamine modulates the excitability of HMNs with other neuromodulators, such as noradrenaline, serotonin and orexin. We think that these findings should provide an important new direction for drug development for the treatment of obstructive sleep apnea.